A case report of advanced hepatocellular carcinoma treated with hepatic arterial infusion chemotherapy and sorafenib combination therapy followed by metastasectomy of lung and muscle metastases - Sang Yi Moon; Sang Young Han; Yang-Hyun Baek (Journal of Liver Cancer, 2022)
Currently, various tyrosine kinase inhibitors and immune checkpoint inhibitors have been suggested in the treatment guidelines for advanced hepatocellular carcinoma (HCC). However, sorafenib was the only systemic drug approved 10 years ago. In 2010, a woman diagnosed with HCC rupture and multiple lung metastases visited our hospital. At the time of visiting our hospital, she had undergone transarterial chemoembolization at another hospital to control bleeding due to HCC rupture. We treated her with hepatic arterial infusion chemotherapy and sorafenib combination therapy to increase the control of intrahepatic tumors in consideration of the modest efficacy of sorafenib. The intrahepatic tumor was almost controlled. Metastasectomy was performed to control lung oligometastasis. Subsequently, additional muscle metastasis was confirmed, and metastasectomy was performed. Although this is a very rare case, it shows that a multidisciplinary approach can improve the prognosis of patients with HCC.